Identification of a Novel Heterozygous De Novo 7-bp Frameshift Deletion in PBX1 by Whole-Exome Sequencing Causing a Multi-Organ Syndrome Including Bilateral Dysplastic Kidneys and Hypoplastic Clavicles - Riedhammer, Korbinian Maria; Siegel, Corinna; Alhaddad, Bader; Montoya, Carmen; Kovacs-Nagy, Reka; Wagner, Matias; Meitinger, Thomas; Hoefele, Julia (Frontiers in Pediatrics, 2017)
Introduction: Congenital anomalies of the kidney and urinary tract (CAKUT) represent the primary cause of chronic kidney disease in children. Many genes have been attributed to the genesis of this disorder. Recently, haploinsufficiency of PBX1 caused by microdeletions has been shown to result in bilateral renal hypoplasia and other organ malformations. Material and Methods: Here, we report on a 14 year old male patient with congenital bilateral dysplastic kidneys, cryptorchidism, hypoplastic clavicles, developmental delay, impaired intelligence, and minor dysmorphic features. Presuming a syndromic origin, we performed SNP array analysis to scan for large copy number variations (CNVs) followed by whole-exome sequencing (WES). Sanger sequencing was done to confirm the variant’s de novo status. Results: SNP array analysis did not reveal any microdeletions or –duplications larger than 50 or 100kb, respectively. WES identified a novel heterozygous 7bp frameshift deletion in PBX1 (c.413_419del, p.Gly138Valfs*40) resulting in a loss-of-function. The de novo status could be confirmed by Sanger sequencing. Discussion: By WES, we identified a novel heterozygous de novo 7bp frameshift deletion in PBX1. Our findings expand the spectrum of causative variants in PBX1-related CAKUT. In this case, WES proved to be the apt technique to detect the variant responsible for the patient’s phenotype, as single gene testing is not feasible given the multitude of genes involved in CAKUT and SNP array analysis misses rare single nucleotide variants and small Indels.